Acute and chronic in vivo effects of exposure to nicotine and propylene glycol from an E-cigarette on mucociliary clearance in a murine model. (16th April 2017) - Laube, Beth L.; Afshar-Mohajer, Nima; Koehler, Kirsten; Chen, Gang; Lazarus, Philip; Collaco, Joseph M.; McGrath-Morrow, Sharon A.
Abstract: Objective: To determine the effect of an acute (1 week) and chronic (3 weeks) exposure to E-cigarette (E-cig) emissions on mucociliary clearance (MCC) in murine lungs. Methods: C57BL/6 male mice (age 10.5 ± 2.4 weeks) were exposed for 20 min/day to E-cigarette aerosol generated by a Joyetech 510-T ® E-cig containing either 0% nicotine (N)/propylene glycol (PG) for 1 week ( n = 6), or 3 weeks ( n = 9), or 2.4% N/PG for one week ( n = 6), or 3 weeks ( n = 9), followed by measurement of MCC. Control mice ( n = 15) were not exposed to PG alone, or N/PG. MCC was assessed by gamma camera following aspiration of 99m technetium aerosol and was expressed as the amount of radioactivity removed from both lungs over 6 hours (MCC6hrs). Venous blood was assayed for cotinine levels in control mice and in mice exposed for 3-weeks to PG alone and N/PG. Results: MCC6hrs in control mice and in mice acutely exposed to PG alone and N/PG was similar, averaging (±1 standard deviation) 8.6 ± 5.2%, 7.5 ± 2.8% and 11.2 ± 5.9%, respectively. In contrast, chronic exposure to PG alone stimulated MCC6hrs (17.2 ± 8.0)% and this stimulation was significantly blunted following chronic exposure to N/PG (8.7 ± 4.6)% ( p < .05). Serum cotinine levels were <0.5 ng/ml in control mice and in mice exposed to PG alone, whereas, N/PG exposed mice averaged 14.6 ± 12.0 ng/ml. Conclusions: In this murine model, a chronic, daily, 20 min-exposure to N/PG, but not an acute exposure, slowed MCC, compared to exposure to PG alone and led to systemic absorption of nicotine.